2019
DOI: 10.1186/s13568-019-0849-7
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol and plant growth promoting potential of phylogenetically new Streptomyces sp. MR14 of rhizospheric origin

Abstract: The detrimental effects of synthetic fungicides have increased the emphasis for biological control as an effective and safe sustainable alternative method. In the present work, a potent rhizospheric actinobacterium MR14 showed broad spectrum antifungal and plant growth promoting activities indicating the potential to fulfill the need. Phylogenetic analysis confirmed that the isolate could be assigned as new species of the Streptomyces , coded as Streptomyces sp. MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 40 publications
(49 reference statements)
0
46
0
Order By: Relevance
“…Many studies have reported that Streptomyces can produce abundant metabolites, which play various roles in agriculture such as plant-promoting and against phytopathogens 80,81 . The wheat bran was used as a low-cost medium in the present study under solid-state fermentation (SSF) and the metabolites may affect the growth of tomato.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that Streptomyces can produce abundant metabolites, which play various roles in agriculture such as plant-promoting and against phytopathogens 80,81 . The wheat bran was used as a low-cost medium in the present study under solid-state fermentation (SSF) and the metabolites may affect the growth of tomato.…”
Section: Discussionmentioning
confidence: 99%
“…Biological control agent treatments did not affect the shoot weight, and root weight was significantly lower for all BCA treatments with respect to the untreated control at the end of the second growing season (3‐year‐old plants). The impact of BCA treatments on grapevine development was very variable on previous research 29,72,73 . Trichoderma spp.…”
Section: Discussionmentioning
confidence: 91%
“…For phylogenetic classi cation of bacteria, sequencing of encoding 16S rRNA gene were aligned against identi ed strains using ClustalW in MEGA X software. The phylogenetic analysis of the identi ed eight strains was conducted with related species their accession numbers were obtained from (Kaur, et al 2019b). To show their phylogenetic relationships (Figure 5) the evolutionary history was inferred by using the Maximum Likelihood method, Tamura-Nei model and Neighbor-Joining method for initial tree.…”
Section: Phylogenetic Analysismentioning
confidence: 99%